2000
DOI: 10.1097/00000539-200002000-00012
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Incidence of the Oculocardiac and Oculorespiratory Reflexes During Sevoflurane or Halothane Anesthesia for Strabismus Surgery in Children

Abstract: Some children experience a sudden slowing of the heart and impaired breathing when the surgeon pulls on the eye muscles during squint operations under anesthesia. Sevoflurane, a recently developed anesthetic vapor, may reduce this problem when compared with the established vapor halothane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 16 publications
3
17
0
1
Order By: Relevance
“…Several studies confirm that OCR is seen more often with halothane than with sevoflurane and isoflurane (15,16). In our study, bradycardia was seen in 29% (group R) and up to 53% (group S) of halothane anesthetics; in another study the frequency was 79% (15). In this latter study, ventilation was spontaneous, and 11 of the 51 children hypoventilated (SpO 2 < 95%, ETCO 2 > 60 mmHg).…”
Section: Discussionsupporting
confidence: 77%
“…Several studies confirm that OCR is seen more often with halothane than with sevoflurane and isoflurane (15,16). In our study, bradycardia was seen in 29% (group R) and up to 53% (group S) of halothane anesthetics; in another study the frequency was 79% (15). In this latter study, ventilation was spontaneous, and 11 of the 51 children hypoventilated (SpO 2 < 95%, ETCO 2 > 60 mmHg).…”
Section: Discussionsupporting
confidence: 77%
“…The continuous infusion of remifentanil induced more change in heart rate following EOM traction than sevoflurane. Allison et al [13] concluded that sevoflurane depressed vagal activity more than halothane. Bradycardia was less pronounced in patients receiving sevoflurane, when OCR happened.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the duration of surgical vagal stimulation was uncertain, and the strength of surgical stimuli is widely different in various surgical procedures, it was unethical to apply equally predetermined doses of sevoflurane during the study period. Previous studies [19,20] have suggested that inappropriate anesthetic depth increases the incidence of the oculocardiac reflex during pediatric strabismus surgery. In this regard, we compared the sevoflurane concentrations and BIS values in both groups at the moment of significant reflex bradycardia, and these were comparable with respect to anesthetic depth.…”
Section: Discussionmentioning
confidence: 99%